2010
DOI: 10.1007/s00192-009-1046-z
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial comparing pelvic floor muscle training to a Pilates exercise program for improving pelvic muscle strength

Abstract: Further study is required to determine if Pilates can actually treat pelvic floor dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
95
1
18

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(116 citation statements)
references
References 21 publications
2
95
1
18
Order By: Relevance
“…The level of difficulty of each exercise will be determined individually for each participant, and the exercises will progress in difficulty in response to reductions in the postural compensations presented by the participant. 2,18,25 After the 6-month follow-up period, treatment using Pilates-based exercises will also be offered to participants in the Booklet Group.…”
Section: Interventionsmentioning
confidence: 99%
“…The level of difficulty of each exercise will be determined individually for each participant, and the exercises will progress in difficulty in response to reductions in the postural compensations presented by the participant. 2,18,25 After the 6-month follow-up period, treatment using Pilates-based exercises will also be offered to participants in the Booklet Group.…”
Section: Interventionsmentioning
confidence: 99%
“…As a contrast to that study, our intention was to investigate the shortterm effects, which resulted in 8 weeks of exercise. Menacho et al [18] found a significant increase in electromyographic activity in back extensor muscles [19]. They investigated healthy women and used traditional mat Pilates exercises similar to this study.…”
Section: Discussionmentioning
confidence: 60%
“…In this study, control group (Group-2) did not have any exercises and this may have caused us to find different results than the ones given in reference. Culligan et al [19] compared a standardized physical therapybased pelvic floor muscles training program with a standardized Pilates program in regards to improvement of pelvic floor muscle strength. They reported that both groups demonstrated improved strength at the end of the study [20].…”
Section: Discussionmentioning
confidence: 99%
“…Studies that investigated the stiffness of the muscle during core training (Wang & Li, 2007) and applications of a new training to improve the performance of elite gymnasts are almost non-existent. Recently, pilates has gained attention as an equipment-using core training method (Critchley, Pierson, & Battersby, 2011;Culligan et al, 2010;Emery, De Serres, McMillan, & Cote, 2010;Irez, Ozdemir, Evin, Irez, & Korkusuz, 2011;Kloubec, 2010;. Pilates is a regulatory exercise (contrology) developed for a neutral spine.…”
mentioning
confidence: 99%